ANALISIS KUALITATIF FORMALDEHID PADA IKAN ASIN YANG DIJUAL DI PASAR BAWAH KOTA PEKANBARU - Mustika Furi (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2015)
Formaldehyde or better known as formalin is one of the food additives that are prohibited and should not be added to the diet according to thelegislation in force. The method used is a qualitative analysis using the reagent kromatofat acid and resorcinol. This study aims to determine thepresence or absence of formaldehyde in salted fish sold in the Pasar Bawah Pekanbaru. Salted fish sampling method used is purposive samplingmethod. The results of a sensitivity test using a chemical reaction reagent kromatofat acid and resorcinol at each concentration as follows: 0.5; 1; 1.5;2; and 2.5 ppm obtained the same results that both kromatofat acid and resorcinol reagent has a minimum sensitivity at a concentration of 1 ppm givepink-purple and purple rings / purple. The results of this study show that 4 out of 10 samples of different types of salted fish sold in Pasar BawahPekanbaru positive for formaldehyde, which is salted fish species: gabur, jambal roti, kembung, dan layur